Walkability and Its Relationships With Health, Sustainability, and Livability: Elements of Physical Environment and Evaluation Frameworks - Baobeid, Abdulla; Koç, Muammer; Al-Ghamdi, Sami G. (Frontiers in Built Environment, 2021)
Urban sprawl and increasing population density in urban centers create the challenge to finding ways of sustainable transportation solutions that preserve the convenience of residents while reducing emissions. Therefore, walkability is a core urban design element due being advantageous on to three fronts: health, livability, and sustainability. Adopting walkability as urban solution relieves conceptual and practical tensions between the individualistic interests manifested in the desire to own and use private cars, and the need to reduce transportation-based consumption This review advocates that long-term health benefits from walking and physical activity are the premier incentive to repurpose our cities to be more sustainable and more walking friendly, and spark behavioral change into reducing car dependency for all daily transportations. The review inspects physical elements of the built environment that make the walking trip feasible and desirable, such as connectivity, accessibility, and closeness of destination points, presence of greenness and parks, commercial retail, and proximity to transit hubs and stations. Hence, this review explores a few popular walkability evaluation indices and frameworks that employ subjective, objective and/or distinctive methods within variant environmental, cultural, and national context. There is a need for rigorous evaluation tools of walkability for policy makers and designers, yet there is no unified universal standardized walkability theory. Furthermore, there is a lack of emphasis on air quality and thermal stress in the design for walkability, despite the being a major factor in in taking the decision to walk and the possibility of nullifying any health benefits from walking. Research opportunities in the field of walkability can leverage location tracking from smart devices and identify the interaction pattens of pedestrians with other transportation modes, especially for those with fundamental movement challenges such as wheelchair users.